Magnesium oxide foamed ceramic and preparation process thereof

By using waterproof modification and zirconia toughening agent in magnesium oxide foam ceramics, combined with the optimized particle size distribution and water-based binder system, the problem of insufficient thermal shock resistance and yield of magnesium oxide foam ceramics is solved, and higher mechanical properties and production efficiency are achieved.

CN119613149APending Publication Date: 2025-03-14山西富谦特种陶瓷有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510098930.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing magnesium oxide foam ceramics have low thermal shock resistance and yield, and are prone to hydration reactions at high temperatures, resulting in structural damage and degradation of performance.

Method used

By mixing the waterproof magnesium oxide, zirconium oxide powder, toughening material and sintering aid, a magnesium oxide-based mixture is formed, and a hydrophobic silicone is used in the aqueous binder system to coat the magnesium oxide powder to avoid hydration reactions, while optimizing the particle size ratio of the magnesium oxide powder to form a wide particle size distribution.

Benefits of technology

The compressive strength, high temperature resistance and thermal shock resistance of magnesium oxide foam ceramics are improved, and the porosity and defects in the sintering process are reduced, and the yield rate is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses magnesium oxide foamed ceramic and a preparation process thereof, and relates to the technical field of foamed ceramic processing, and the preparation process comprises the following steps: mixing waterproof magnesium oxide, zirconium oxide powder, a toughening material and a sintering aid to obtain a magnesium oxide-based mixture, and mixing the magnesium oxide-based mixture, a binder and deionized water to obtain molding slurry; the preparation method comprises the following steps: optimizing the particle size distribution of magnesium oxide, carrying out hydration resistance modification on the magnesium oxide, enhancing the magnesium oxide in an aqueous binder environment by using a flexibilizer composed of zirconium oxide, whiskers and fibers, and carrying out high-temperature sintering to obtain the magnesium oxide-based ceramic with high void ratio. The normal-temperature compressive strength and the high-temperature bending strength of the magnesium oxide-based ceramic are effectively improved, and the thermal shock resistance and the production yield of the magnesium oxide-based ceramic are also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of foam ceramic processing, in particular to a magnesium oxide foam ceramic and a preparation process thereof. Background Art

[0002] With the rapid development of new energy vehicles and the layout of lightweight industry, the demand for magnesium alloys is increasing. Magnesium oxide foam ceramics with high-efficiency filtration performance have also attracted great attention. Magnesium oxide foam ceramic filters have a good three-dimensional mesh skeleton structure, which can filter various inclusions and impurities in magnesium and magnesium alloy melts, improve the intrinsic quality of castings and reduce defects.

[0003] A Chinese patent document with publication number CN101785944A discloses a method for preparing a magnesium oxide foam ceramic filter for filtering magnesium and magnesium alloy melts. The polyurethane foam template is soaked in a 10% sodium hydroxide aqueous solution at 50°C for 30 minutes, then washed with water and dried, and then fused magnesium oxide, magnesium fluoride and water are ball-milled according to a mass ratio to obtain a uniform water-based dispersed slurry. The obtained product has chemical stability in magnesium and magnesium alloy melts, does not pollute magnesium and magnesium alloy melts, and has good adsorption and filtering effects on non-metallic impurities therein, and is suitable for filtering and purifying magnesium and magnesium alloy melts;

[0004] A Chinese patent document with publication number CN116161981A discloses a method for preparing anhydrous magnesium oxide foam ceramics, including pretreatment of magnesium oxide powder, preparation of molding slurry, slurry molding, drying, and sintering. The method for preparing anhydrous magnesium oxide foam ceramics provides large-scale, low-cost industrial preparation.

[0005] Magnesium oxide foam ceramics are mainly used to filter magnesium or magnesium alloys melted at high temperatures. Since magnesium is very active in chemical properties, it will react with many materials such as SiO 2 , AL 2 O 3 In order to avoid the introduction of impurities during high-temperature filtration, it is usually necessary to strictly control the impurity composition of magnesium oxide foam ceramics;

[0006] However, due to the large thermal expansion coefficient of magnesium oxide, the thermal shock resistance of magnesium oxide foam ceramics is poor. In actual use, the filter sheet often breaks during use, which causes slag inclusion in the casting. In addition, during the production of magnesium oxide foam ceramics with water-based binders, magnesium oxide is easily hydrated, resulting in the overall strength and yield of the produced magnesium oxide foam ceramics needing to be further improved.

[0007] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0008] The object of the present invention is to provide a magnesium oxide foam ceramic and a preparation process thereof, so as to solve the technical problem in the prior art that the overall performance and yield rate of magnesium oxide foam ceramic including thermal shock resistance need to be further improved.

[0009] The purpose of the present invention can be achieved by the following technical solution: A preparation process of magnesium oxide foam ceramics, comprising the following steps:

[0010] S1, mixing waterproof magnesium oxide, zirconium oxide powder, toughening material, and sintering aid to obtain a magnesium oxide-based mixture;

[0011] S2, mixing the magnesium oxide-based mixture, the binder and deionized water to obtain a forming slurry;

[0012] S3, rolling the formed slurry to obtain a magnesium oxide foam ceramic body;

[0013] S4, sintering the magnesium oxide foam ceramic body to obtain magnesium oxide foam ceramic.

[0014] Furthermore, in step S1, the weight ratio of waterproof magnesium oxide, zirconium oxide powder, toughening material and sintering aid is 70-90:15-30:1-5:0.5-2, the content of aluminum oxide and silicon dioxide in the zirconium oxide powder is less than 0.4%, the zirconium oxide powder has a monoclinic crystal form and a particle size of 1000 mesh-3000 mesh, the toughening material is one or more of magnesium oxide short fibers, magnesium oxide whiskers, magnesium borate whiskers and zirconium oxide short fibers; the sintering aid is one of calcium fluoride or calcium borate.

[0015] Furthermore, the preparation method of the waterproof magnesium oxide is: placing magnesium oxide powder and a waterproofing auxiliary agent in a mixer, and mixing for 30-50 minutes to obtain the waterproof magnesium oxide.

[0016] Furthermore, the weight ratio of the magnesium oxide to the waterproofing agent is 100:0.5-2, the magnesium oxide powder is composed of high-purity fused magnesia with a particle size of 200 mesh and high-purity fused magnesia with a particle size of 600 mesh in a weight ratio of 3-4:1-2, the content of high-purity fused magnesia is higher than 99.4%, and the contents of alumina and silicon dioxide in the high-purity fused magnesia are both lower than 0.2%; the waterproofing agent is methylsiloxane or dimethyl silicone oil.

[0017] Furthermore, in step S2, the weight ratio of the magnesium oxide-based mixture, the binder and the deionized water is 100:10-15:5-15, and the binder is any one of polyvinyl alcohol, polyethylene glycol and dextrin.

[0018] Furthermore, in step S3, the forming method of the magnesium oxide foam ceramic body is:

[0019] A1, conveying the polyurethane foam to a roller press soaked in the forming slurry, passing through a pressing roller for the first roller pressing and slurry dipping, and drying to obtain the first slurry dipping foam;

[0020] A2. The foam obtained by the first impregnation is transported to a roller press soaked in the forming slurry, and the foam is pressed and impregnated for the second time through a pressing roller, and then dried to obtain a magnesium oxide foam ceramic body.

[0021] Further, in step A1, the density of the polyurethane foam is 0.02-0.03 g / cm 3 The drying temperature is 100-110℃, the drying time is 30-50min, and the density of the first slurry foam is 0.4-0.6g / cm 3 In step A2, the drying temperature is 110-120°C, the drying time is 30-50min, and the density of the magnesium oxide foam ceramic body is 0.7-0.9g / cm 3 .

[0022] Furthermore, in step S4, the sintering temperature is 1300-1400° C., and the sintering time is 16 hours.

[0023] The present invention further provides a magnesium oxide foam ceramic, which is prepared by using the above-mentioned magnesium oxide foam ceramic preparation process. The magnesium oxide foam ceramic is used for filtering magnesium or magnesium alloy melt.

[0024] The present invention has the following beneficial effects:

[0025] 1. The magnesium oxide foam ceramic of the present invention uses polyurethane foam as a carrier, is roll-formed by forming slurry, and is calcined at high temperature to promote the decomposition of the polyurethane foam carrier to form a green body with a porous structure. At high temperature, the crystal grains in the ceramic will gradually grow, the gaps between the ceramic particles will gradually decrease, the bonding force between the particles will be enhanced, and the densification of the ceramic will occur. In addition, the growth of the crystal grains helps to reduce the number of grain boundaries, reduce the grain boundary energy, and improve the hardness and strength of the ceramic. Under the process conditions of using an aqueous binder, the magnesium oxide is hydrophobically modified to avoid hydration reaction, which causes the magnesium oxide foam ceramic to be edge-missing and slag-falling, thereby improving the yield rate of the magnesium oxide foam ceramic.

[0026] 2. The magnesium oxide foam ceramic of the present invention is modified by coating magnesium oxide powder with hydrophobic siloxane to prevent water molecules from penetrating into the interior of magnesium oxide particles, thereby preventing magnesium oxide from undergoing hydration reaction in an aqueous binder system to cause volume expansion, structural damage and performance degradation. By optimizing the particle size ratio of magnesium oxide powder, a wider particle size distribution is formed in the magnesium oxide ceramic body, which can promote more uniform grain growth, avoid the formation of oversized or undersized grains, and help to form a more compact particle stacking during the sintering process, reduce porosity, thereby improving the densification degree of the material and improving the material quality. The room temperature compressive strength and high temperature resistance of the material are improved, and the wider particle size distribution helps to reduce the porosity, reduce the thermal stress concentration points, reduce the defects and crack formation during the sintering process, thereby improving the yield and thermal shock resistance. When selecting magnesium oxide raw materials, high-density fused magnesium oxide with a density of up to 3.4 is selected, which can effectively increase the solid content of the slurry, thereby reducing the gaps between the magnesium oxide particles, improving the density and strength of the final product, and limiting the content of impurities such as alumina and silica, to avoid contamination of magnesium alloy castings when filtering the magnesium alloy melt.

[0027] 3. The magnesium oxide foam ceramic of the present invention adopts monoclinic zirconium oxide as the second phase, and the chemical properties of zirconium oxide are stable. The zirconium oxide ceramic does not react chemically with the magnesium metal melt. Zirconia is added to the magnesium oxide foam ceramic as the second phase, and the thermal expansion mismatch between the monoclinic zirconium oxide and the main crystal phase periclase causes a certain number of microcracks to be generated inside the sintered sample. During the sintering and cooling process, the zirconium oxide undergoes a martensitic phase transformation to generate microcracks. The microcracks improve the fracture toughness of the sample, thereby improving the thermal shock resistance of the product. Short fibers or whiskers are used for fiber reinforcement and toughening, and the characteristics of whisker-reinforced and toughened ceramics are utilized to improve the thermal shock resistance, room temperature compression resistance and high temperature resistance of the magnesium oxide foam ceramic. By adopting calcium fluoride or calcium borate compounds as sintering aids, the sintering temperature of the magnesium oxide foam ceramic can be significantly reduced, and the fusion of metal magnesium oxide with calcium and toughening materials is promoted under the action of high temperature. At the same time, magnesium alloys cannot reduce calcium compounds, thereby avoiding contamination of magnesium or magnesium alloy casting raw materials during melt filtration. DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] In the present invention, the content of high-purity fused magnesia is higher than 99.4%, and the content of alumina and silicon dioxide in the high-purity fused magnesia is lower than 0.2%;

[0030] In the present invention, the contents of alumina and silica in the zirconium oxide powder are both less than 0.4%, and the crystal form of the zirconium oxide powder is monoclinic;

[0031] In the present invention, the density of the polyurethane foam is 0.02-0.03 g / cm 3 ;

[0032] In the present invention, the polyvinyl alcohol is PVA 17-92;

[0033] In the present invention, the polyethylene glycol is PEG-4000;

[0034] In the present invention, dextrin is cyclodextrin.

[0035] Example 1

[0036] This embodiment provides a preparation process of magnesium oxide foam ceramics, comprising the following steps:

[0037] S1. Preparation of waterproof magnesium oxide

[0038] The high-purity fused magnesia with a particle size of 200 mesh and the high-purity fused magnesia with a particle size of 600 mesh are mixed in a weight ratio of 3:1 to obtain magnesium oxide powder;

[0039] Magnesium oxide powder and methylsiloxane were placed in a mixer at a weight ratio of 100:0.5 and mixed for 30 minutes to obtain waterproof magnesium oxide.

[0040] S2. Preparation of magnesium oxide-based mixture

[0041] Weigh by weight: 70 parts of waterproof magnesium oxide, 15 parts of zirconium oxide powder with a particle size of 1000 mesh, 1 part of magnesium oxide short fiber, and 0.5 parts of calcium fluoride, and mix them to obtain a magnesium oxide-based mixture.

[0042] S3. Preparation of molding slurry

[0043] Weigh by weight: 100 parts of magnesium oxide-based mixture, 10 parts of polyvinyl alcohol and 5 parts of deionized water, add into a high-speed disperser, set the dispersion speed of the high-speed disperser to 1000 rpm, mix and disperse for 20 minutes to obtain a molding slurry.

[0044] S4. Preparation of magnesium oxide ceramic body

[0045] The polyurethane foam was transported to a roller press soaked in the molding slurry, and the first roller pressing and slurry dipping was carried out through the roller. The polyurethane foam with the slurry dipping was transported to a drying oven at a temperature of 100°C and dried for 30 minutes to obtain a density of 0.4 g / cm 3 The first dip foam;

[0046] The first impregnated foam was transported to a roller press soaked in the molding slurry, and the second roller pressing impregnation was carried out through the pressing roller. The polyurethane foam with the impregnation slurry was transported to a drying oven at a temperature of 110°C and dried for 30 minutes to obtain a density of 0.7 g / cm 3 Magnesium oxide foam ceramic body.

[0047] S5. Preparation of magnesium oxide foam ceramics

[0048] The magnesium oxide foam ceramic body is transferred to a tube furnace, the temperature of the tube furnace is increased to 1300° C., the furnace is kept warm for sintering for 16 hours, and the temperature is naturally lowered to room temperature to obtain magnesium oxide foam ceramic.

[0049] Example 2

[0050] This embodiment provides a preparation process of magnesium oxide foam ceramics, comprising the following steps:

[0051] S1. Preparation of waterproof magnesium oxide

[0052] The high-purity fused magnesia with a particle size of 200 mesh and the high-purity fused magnesia with a particle size of 600 mesh are mixed in a weight ratio of 3.5:1.5 to obtain magnesium oxide powder;

[0053] Magnesium oxide powder and dimethyl silicone oil were placed in a mixer at a weight ratio of 100:1.25 and mixed for 40 minutes to obtain waterproof magnesium oxide.

[0054] S2. Preparation of magnesium oxide-based mixture

[0055] Weigh out by weight: 80 parts of waterproof magnesium oxide, 18 parts of zirconium oxide powder with a particle size of 2000 mesh, 3 parts of magnesium oxide whiskers, and 1.3 parts of calcium borate, and mix them to obtain a magnesium oxide-based mixture.

[0056] S3. Preparation of molding slurry

[0057] Weigh by weight: 100 parts of magnesium oxide-based mixture, 13 parts of polyethylene glycol and 10 parts of deionized water, add into a high-speed disperser, set the dispersion speed of the high-speed disperser to 1050 rpm, mix and disperse for 25 minutes to obtain a molding slurry.

[0058] S4. Preparation of magnesium oxide ceramic body

[0059] The polyurethane foam was transported to a roller press soaked in the molding slurry, and the first roller pressing and slurry dipping was carried out through the pressing roller. The polyurethane foam with the slurry dipping was transported to a drying oven at a temperature of 105°C and dried for 40 minutes to obtain a density of 0.5 g / cm 3 The first dip foam;

[0060] The first impregnated foam was transported to a roller press soaked in the molding slurry, and the second roller pressing impregnation was carried out through the pressing roller. The polyurethane foam with the impregnation material was transported to a drying oven at a temperature of 115°C and dried for 40 minutes to obtain a density of 0.8 g / cm 3 Magnesium oxide foam ceramic body.

[0061] S5. Preparation of magnesium oxide foam ceramics

[0062] The magnesium oxide foam ceramic body is transferred to a tube furnace, the temperature of the tube furnace is increased to 1350° C., the furnace is kept warm and sintered for 16 hours, and the temperature is naturally cooled to room temperature to obtain magnesium oxide foam ceramic.

[0063] Example 3

[0064] This embodiment provides a preparation process of magnesium oxide foam ceramics, comprising the following steps:

[0065] S1. Preparation of waterproof magnesium oxide

[0066] The high-purity fused magnesia with a particle size of 200 mesh and the high-purity fused magnesia with a particle size of 600 mesh are mixed in a weight ratio of 4:2 to obtain magnesium oxide powder;

[0067] Magnesium oxide powder and methylsiloxane were placed in a mixer at a weight ratio of 100:2 and mixed for 50 minutes to obtain waterproof magnesium oxide.

[0068] S2. Preparation of magnesium oxide-based mixture

[0069] Weigh by weight: 90 parts of waterproof magnesium oxide, 30 parts of zirconium oxide powder with a particle size of 3000 mesh, 2 parts of magnesium borate whiskers, 3 parts of zirconium oxide short fibers, and 2 parts of calcium fluoride, and mix to obtain a magnesium oxide-based mixture.

[0070] S3. Preparation of molding slurry

[0071] Weigh by weight: 100 parts of magnesium oxide-based mixture, 15 parts of dextrin and 15 parts of deionized water, add into a high-speed disperser, set the dispersion speed of the high-speed disperser to 1100 rpm, mix and disperse for 30 minutes, and obtain a molding slurry.

[0072] S4. Preparation of magnesium oxide ceramic body

[0073] The polyurethane foam was transported to a roller press soaked in the molding slurry, and the first roller pressing and slurry dipping was carried out through the pressing roller. The polyurethane foam with the slurry dipping was transported to a drying oven at a temperature of 110°C and dried for 50 minutes to obtain a density of 0.6 g / cm 3 The first dip foam;

[0074] The first impregnated foam was transported to a roller press soaked in the molding slurry, and the second roller pressing impregnation was carried out through the pressing roller. The polyurethane foam with the impregnated slurry was transported to a drying oven at a temperature of 120°C and dried for 50 minutes to obtain a density of 0.9 g / cm 3 Magnesium oxide foam ceramic body.

[0075] S5. Preparation of magnesium oxide foam ceramics

[0076] The magnesium oxide foam ceramic body is transferred to a tube furnace, the temperature of the tube furnace is increased to 1400° C., the furnace is kept warm and sintered for 16 hours, and the temperature is naturally cooled to room temperature to obtain magnesium oxide foam ceramic.

[0077] Comparative Example 1

[0078] This comparative example provides a preparation process of magnesium oxide foam ceramics, comprising the following steps:

[0079] S1. Preparation of magnesium oxide powder

[0080] High-purity fused magnesia with a particle size of 200 mesh and high-purity fused magnesia with a particle size of 600 mesh are mixed in a weight ratio of 4:2 to obtain magnesium oxide powder.

[0081] S2. Preparation of magnesium oxide-based mixture

[0082] Weigh by weight: 90 parts of magnesium oxide powder, 30 parts of zirconium oxide powder with a particle size of 3000 meshes, 2 parts of magnesium borate whiskers, 3 parts of zirconium oxide short fibers, and 2 parts of calcium fluoride, and mix to obtain a magnesium oxide-based mixture.

[0083] S3. Preparation of molding slurry

[0084] Weigh by weight: 100 parts of magnesium oxide-based mixture, 15 parts of dextrin and 15 parts of deionized water, add into a high-speed disperser, set the dispersion speed of the high-speed disperser to 1100 rpm, mix and disperse for 30 minutes, and obtain a molding slurry.

[0085] S4. Preparation of magnesium oxide ceramic body

[0086] The polyurethane foam was transported to a roller press soaked in the molding slurry, and the first roller pressing and slurry dipping was carried out through the pressing roller. The polyurethane foam with the slurry dipping was transported to a drying oven at a temperature of 110°C and dried for 50 minutes to obtain a density of 0.6 g / cm 3 The first dip foam;

[0087] The first impregnated foam was transported to a roller press soaked in the molding slurry, and the second roller pressing impregnation was carried out through the pressing roller. The polyurethane foam with the impregnated slurry was transported to a drying oven at a temperature of 120°C and dried for 50 minutes to obtain a density of 0.9 g / cm 3 Magnesium oxide foam ceramic body.

[0088] S5. Preparation of magnesium oxide foam ceramics

[0089] The magnesium oxide foam ceramic body is transferred to a tube furnace, the temperature of the tube furnace is increased to 1400° C., the furnace is kept warm and sintered for 16 hours, and the temperature is naturally cooled to room temperature to obtain magnesium oxide foam ceramic.

[0090] Comparative Example 2

[0091] This comparative example provides a preparation process of magnesium oxide foam ceramics, comprising the following steps:

[0092] S1. Preparation of waterproof magnesium oxide

[0093] The high-purity fused magnesia with a particle size of 200 mesh and the high-purity fused magnesia with a particle size of 600 mesh are mixed in a weight ratio of 4:2 to obtain magnesium oxide powder;

[0094] Magnesium oxide powder and methylsiloxane were placed in a mixer at a weight ratio of 100:2 and mixed for 50 minutes to obtain waterproof magnesium oxide.

[0095] S2. Preparation of magnesium oxide-based mixture

[0096] Weigh by weight: 90 parts of waterproof magnesium oxide, 2 parts of magnesium borate whiskers, 3 parts of zirconium oxide short fibers, and 2 parts of calcium fluoride, and mix to obtain a magnesium oxide-based mixture.

[0097] S3. Preparation of molding slurry

[0098] Weigh by weight: 100 parts of magnesium oxide-based mixture, 15 parts of dextrin and 15 parts of deionized water, add into a high-speed disperser, set the dispersion speed of the high-speed disperser to 1100 rpm, mix and disperse for 30 minutes, and obtain a molding slurry.

[0099] S4. Preparation of magnesium oxide ceramic body

[0100] The polyurethane foam was transported to a roller press soaked in the molding slurry, and the first roller pressing and slurry dipping was carried out through the pressing roller. The polyurethane foam with the slurry dipping was transported to a drying oven at a temperature of 110°C and dried for 50 minutes to obtain a density of 0.6 g / cm 3 The first dip foam;

[0101] The first impregnated foam was transported to a roller press soaked in the molding slurry, and the second roller pressing impregnation was carried out through the pressing roller. The polyurethane foam with the impregnated slurry was transported to a drying oven at a temperature of 120°C and dried for 50 minutes to obtain a density of 0.9 g / cm 3 Magnesium oxide foam ceramic body.

[0102] S5. Preparation of magnesium oxide foam ceramics

[0103] The magnesium oxide foam ceramic body is transferred to a tube furnace, the temperature of the tube furnace is increased to 1400° C., the furnace is kept warm and sintered for 16 hours, and the temperature is naturally cooled to room temperature to obtain magnesium oxide foam ceramic.

[0104] Comparative Example 3

[0105] This comparative example provides a preparation process of magnesium oxide foam ceramics, comprising the following steps:

[0106] S1. Preparation of waterproof magnesium oxide

[0107] The high-purity fused magnesia with a particle size of 200 mesh and the high-purity fused magnesia with a particle size of 600 mesh are mixed in a weight ratio of 4:2 to obtain magnesium oxide powder;

[0108] Magnesium oxide powder and methylsiloxane were placed in a mixer at a weight ratio of 100:2 and mixed for 50 minutes to obtain waterproof magnesium oxide.

[0109] S2. Preparation of magnesium oxide-based mixture

[0110] Weigh by weight: 90 parts of waterproof magnesium oxide, 30 parts of zirconium oxide powder with a particle size of 3000 meshes, and 2 parts of calcium fluoride, and mix them to obtain a magnesium oxide-based mixture.

[0111] S3. Preparation of molding slurry

[0112] Weigh by weight: 100 parts of magnesium oxide-based mixture, 15 parts of dextrin and 15 parts of deionized water, add into a high-speed disperser, set the dispersion speed of the high-speed disperser to 1100 rpm, mix and disperse for 30 minutes, and obtain a molding slurry.

[0113] S4. Preparation of magnesium oxide ceramic body

[0114] The polyurethane foam was transported to a roller press soaked in the molding slurry, and the first roller pressing and slurry dipping was carried out through the pressing roller. The polyurethane foam with the slurry dipping was transported to a drying oven at a temperature of 110°C and dried for 50 minutes to obtain a density of 0.6 g / cm 3 The first dip foam;

[0115] The first impregnated foam was transported to a roller press soaked in the molding slurry, and the second roller pressing impregnation was carried out through the pressing roller. The polyurethane foam with the impregnated slurry was transported to a drying oven at a temperature of 120°C and dried for 50 minutes to obtain a density of 0.9 g / cm 3 Magnesium oxide foam ceramic body.

[0116] S5. Preparation of magnesium oxide foam ceramics

[0117] The magnesium oxide foam ceramic body is transferred to a tube furnace, the temperature of the tube furnace is increased to 1400° C., the furnace is kept warm and sintered for 16 hours, and the temperature is naturally cooled to room temperature to obtain magnesium oxide foam ceramic.

[0118] Comparative Example 4

[0119] This comparative example provides a preparation process of magnesium oxide foam ceramics, comprising the following steps:

[0120] S1. Preparation of waterproof magnesium oxide

[0121] Using high-purity fused magnesia with a particle size of 200 mesh as magnesium oxide powder;

[0122] Magnesium oxide powder and methylsiloxane were placed in a mixer at a weight ratio of 100:2 and mixed for 50 minutes to obtain waterproof magnesium oxide.

[0123] S2. Preparation of magnesium oxide-based mixture

[0124] Weigh by weight: 90 parts of waterproof magnesium oxide, 30 parts of zirconium oxide powder with a particle size of 3000 mesh, 2 parts of magnesium borate whiskers, 3 parts of zirconium oxide short fibers, and 2 parts of calcium fluoride, and mix to obtain a magnesium oxide-based mixture.

[0125] S3. Preparation of molding slurry

[0126] Weigh by weight: 100 parts of magnesium oxide-based mixture, 15 parts of dextrin and 15 parts of deionized water, add into a high-speed disperser, set the dispersion speed of the high-speed disperser to 1100 rpm, mix and disperse for 30 minutes, and obtain a molding slurry.

[0127] S4. Preparation of magnesium oxide ceramic body

[0128] The polyurethane foam was transported to a roller press soaked in the molding slurry, and the first roller pressing and slurry dipping was carried out through the pressing roller. The polyurethane foam with the slurry dipping was transported to a drying oven at a temperature of 110°C and dried for 50 minutes to obtain a density of 0.6 g / cm 3 The first dip foam;

[0129] The first impregnated foam was transported to a roller press soaked in the molding slurry, and the second roller pressing impregnation was carried out through the pressing roller. The polyurethane foam with the impregnated slurry was transported to a drying oven at a temperature of 120°C and dried for 50 minutes to obtain a density of 0.9 g / cm 3 Magnesium oxide foam ceramic body.

[0130] S5. Preparation of magnesium oxide foam ceramics

[0131] The magnesium oxide foam ceramic body is transferred to a tube furnace, the temperature of the tube furnace is increased to 1400° C., the furnace is kept warm and sintered for 16 hours, and the temperature is naturally cooled to room temperature to obtain magnesium oxide foam ceramic.

[0132] Data Analysis:

[0133] The room temperature compressive strength, high temperature flexural strength and thermal shock resistance (1100°C) of the magnesium oxide foam ceramic samples prepared in Examples 1-3 and Comparative Examples 1-4 were measured in accordance with the standard GB / T 25139-2010 "Foam ceramic filter for casting".

[0134] According to the formula , calculate the yield of magnesium oxide foam ceramics prepared by the magnesium oxide foam ceramic preparation process provided in Examples 1-3 and Comparative Examples 1-4, where N 成品量 is the number of finished products, N 产量 is the total quantity of magnesium oxide foam ceramics produced. Specific test results are shown in Table 1 below.

[0135] Table 1-Performance test data of the sample

[0136]

[0137] Data Analysis:

[0138] A comparative analysis of the data in Table 1 above shows that the room-temperature compressive strength of the magnesium oxide foam ceramic sample prepared by the present invention reaches 1.46 MPa, the high-temperature flexural strength is 0.89 MPa, the thermal shock resistance reaches 54 times, the yield rate reaches 98.1%, and the performance test data are all better than the comparative example. The present invention optimizes the particle size distribution of magnesium oxide and then performs hydration resistance modification on it, and strengthens magnesium oxide with a toughening agent composed of zirconium oxide, whiskers and fibers in an aqueous binder environment, and obtains magnesium oxide-based ceramics with a high porosity after high-temperature firing, which not only effectively improves the room-temperature compressive strength and high-temperature flexural strength of magnesium oxide-based ceramics, but also improves its thermal shock resistance and production yield.

[0139] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A process for preparing magnesium oxide foam ceramics, characterized in that: The following steps are involved: S1, mixing waterproof magnesium oxide, zirconium oxide powder, toughening material and sintering aid to obtain magnesium oxide-based mixture; S2, mixing the magnesium oxide-based mixture, the binder and deionized water to obtain a forming slurry; S3, rolling the formed slurry to obtain a magnesium oxide foam ceramic body; S4, sintering the magnesium oxide foam ceramic body to obtain magnesium oxide foam ceramic.

2. The process for preparing magnesium oxide foam ceramic according to claim 1, characterized in that: In step S1, the weight ratio of waterproof magnesium oxide, zirconium oxide powder, toughening material and sintering aid is 70-90:15-30:1-5:0.5-2, the content of aluminum oxide and silicon dioxide in the zirconium oxide powder is less than 0.4%, the zirconium oxide powder crystal form is monoclinic, the particle size is 1000 mesh-3000 mesh, the toughening material is one or more of magnesium oxide short fiber, magnesium oxide whisker, magnesium borate whisker and zirconium oxide short fiber; the sintering aid is one of calcium fluoride or calcium borate.

3. The process for preparing magnesium oxide foam ceramic according to claim 1, characterized in that: The preparation method of the waterproof magnesium oxide is as follows: magnesium oxide powder and a waterproofing auxiliary agent are placed in a mixer, and mixed for 30-50 minutes to obtain the waterproof magnesium oxide.

4. The process for preparing magnesium oxide foam ceramic according to claim 3, characterized in that: The weight ratio of the magnesium oxide to the waterproofing agent is 100:0.5-2, the magnesium oxide powder is composed of high-purity fused magnesia with a particle size of 200 mesh and high-purity fused magnesia with a particle size of 600 mesh in a weight ratio of 3-4:1-2, the content of the high-purity fused magnesia is higher than 99.4%, and the contents of alumina and silicon dioxide in the high-purity fused magnesia are both lower than 0.2%; the waterproofing agent is methylsiloxane or dimethyl silicone oil.

5. The process for preparing magnesium oxide foam ceramic according to claim 1, characterized in that: In step S2, the weight ratio of the magnesium oxide-based mixture, the binder and the deionized water is 100:10-15:5-15, and the binder is any one of polyvinyl alcohol, polyethylene glycol and dextrin.

6. The process for preparing magnesium oxide foam ceramic according to claim 1, characterized in that: In step S3, the forming method of the magnesium oxide foam ceramic body is: A1, conveying the polyurethane foam to a roller press soaked in the molding slurry, passing through a pressing roller for the first roller pressing and slurry dipping, and drying to obtain the first slurry dipping foam; A2. The foam obtained by the first impregnation is transported to a roller press soaked in the forming slurry, and the foam is pressed and impregnated for the second time through a pressing roller, and then dried to obtain a magnesium oxide foam ceramic body.

7. The process for preparing magnesium oxide foam ceramic according to claim 6, characterized in that: In step A1, the density of the polyurethane foam is 0.02-0.03 g / cm 3 The drying temperature is 100-110℃, the drying time is 30-50min, and the density of the first slurry foam is 0.4-0.6g / cm 3 In step A2, the drying temperature is 110-120°C, the drying time is 30-50min, and the density of the magnesium oxide foam ceramic body is 0.7-0.9g / cm 3 .

8. The process for preparing magnesium oxide foam ceramic according to claim 1, characterized in that: In step S4, the sintering temperature is 1300-1400° C. and the sintering time is 16 hours.

9. A magnesium oxide foam ceramic, characterized in that: The magnesium oxide foam ceramic is prepared by using a preparation process of magnesium oxide foam ceramic according to any one of claims 1 to 8, and the magnesium oxide foam ceramic is used for filtering magnesium or magnesium alloy melt.

Citation Information

Patent Citations

  • Magnesium oxide ceramic foam filter for filtering magnesium and magnesium alloy melt and preparation method thereof

    CN101785944A

  • Preparation method of anhydrous magnesium oxide foamed ceramic

    CN116161981A